UPAYA MENCIPTAKAN PERILAKU HIDUP BERSIH DAN SEHAT DENGAN RUTIN MENCUCI TANGAN DI SDN SUKABUMI 2 PROBOLINGGO - Ani Anjarwati; Putri Fatimattus Az Zahra; Adenita Faradilla; Dinda Dwi Cantika Tizenanda; Dita Refani Putri; Vegas Albar Pratama (Jurnal Abdi Insani, 2022)
Washing hands using soap and clean running water is an effort to prevent disease through sanitation measures, this activity is also included in the category of Clean and Healthy Lifestyle (PHBS). Hand washing is very important because it is proven to be effective in preventing infection control and the spread of disease. Based on a survey conducted by researchers, there are still many students at SDN Sukabumi 2 Probolinggo City who have not been able to apply hand washing before and after eating. Tri Bhakti activities use the “community education” method. By providing an explanation of the pattern of Clean and Healthy Living Behavior in order to know how to maintain personal hygiene and the environment. After that, students practice directly the application of hand washing to maintain personal health. This activity aims to provide direct training and practicum as well as provide an overview of how to properly wash hands for 40 students in Grades 4 and 5 at SDN Sukabumi 2 Probolinggo City. In the implementation of Tri Bhakti activities, it can run smoothly so that students gain increased knowledge, students can know and apply the material that has been presented. Students are asked to directly apply the steps in washing hands properly according to WHO standards. In addition, students can provide examples of how to keep the environment clean and clean and healthy behavior (PHBS) by disposing of garbage in its place. This Tri Bhakti activity has a good impact on elementary school students, because they become aware of the pattern of Clean and Healthy Living Behavior (PHBS). With this Tri Bhakti socialization, it provides new experiences for the students of SDN Sukabumi 2 Probolinggo City in maintaining personal and environmental hygiene.